An analytical view of the role of sports media in promoting sports culture from the perspective of faculty members at Halabja University - Abdulqadir, Asst.L. Nusaiba Farih; Jabar, Prof.Dr. Raed faeq Abdul; Asad, Prof. Dr. Majid Khuda Pakhsh; Rafiq, Prof. Dr. Haval Khurshid (Sulaimani Journal for Humanities, 2026)
This research aimed to identify the role of media in promoting sports culture among faculty members at Halabja University and to determine the statistical differences in the impact of media on disseminating sports culture at the university based on gender. The researchers adopted a descriptive survey methodology to address the research problem. The research population consisted of 245 faculty members at Halabja University, including 195 males and 50 females. A sample of 60 faculty members was randomly selected using a lottery system. Researchers distributed questionnaires to all members of the sample to collect the required data. Drawing on their personal experiences, as well as previous research and scientific sources, the researchers developed a questionnaire consisting of 24 questions distributed across three axes: sports media, sports culture, and social aspects, with 8 items per axis. Three answer choices (always, sometimes, rarely) were provided, with scores of 3, 2, and 1 respectively. One of the most important conclusions reached by the researchers is that sports media is not fulfilling its role adequately in disseminating sports culture within the University of Halabja. Furthermore, sports media has a significant impact on informing individuals about the latest sports developments and providing them with relevant information.
Keywords: Analytical perspective; sports media; sports culture